Three new remarkable amphipod species (Crustacea: Gammaridae) from springs and subterranean waters of Central Asia - Sidorov, Dmitry; Hou, Zhonge; Sket, Boris (Zootaxa, 2018)
Three new species of the family Gammaridae—Gammarus troglomorphus, sp. n., G. parvioculatus, sp. n. from Lebap Province of Turkmenistan and Tadzocrangonyx alaicus, sp. n. from Batken Region of Kyrgyzstan are described and illustrated. Morphological studies of a closely related Turkmenistan population of G. cf. subaequalis-Garlyk, probably conspecific with Gammarus subaequalis Martynov, 1935 was provided. The affinity of new species to concerned taxa is discussed. To define phylogenetic position of mentioned species DNA barcode data are obtained. Gammarus troglomorphus and G. parvioculatus are close neighbors but exceedingly different morphologically. Gammarus troglomorphus is a troglobiont; G. parvioculatus is an eutroglophile, but with exception of slightly smaller eyes, not troglomorph. Both found only within small areas in the extreme East of Turkmenistan. Gammarus cf. subaequalis-Garlyk seems to extend from the same region far into the eastern Kyrgyzstan.